CATHETER-ASSOCIATED URINARY TRACT INFECTION IN POST-NEUROSURGICAL PATIENTS AT THE CENTER FOR ANESTHESIA AND INTENSIVE CARE, BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To survey the prevalence of catheter-associated urinary tract infection and analyze associated factors among post-neurosurgical patients at the Center for Anesthesia and Intensive Care, Bach Mai Hospital.Methods: A prospective descriptive study was conducted on 242 post-neurosurgical patients with indwelling catheters for ≥ 48 hours from April 2022 to March 2023. Catheter-associated urinary tract infection was diagnosed based on the 2014 CDC criteria. Data were analyzed using SPSS software.Results: The catheter-associated urinary tract infection prevalence was 9.1% with an incidence of 6.8 cases per 1000 catheter-days. Candida were the primary pathogens (66.7%). The catheter-associated urinary tract infection rate in females (24.6%) was significantly higher than in males (12.8%) (p = 0.03). Catheter-associated urinary tract infection was significantly associated with catheter duration ≥ 10 days and ICU stay ≥ 10 days (p < 0.05). Notably, 91.7% of patients had clear urine at the time of diagnosis.Conclusions: Catheter-associated urinary tract infection prevalence in neurosurgical patients is substantial with subtle clinical symptoms. Reducing catheter duration and enhancing fungal infection control are key strategies to minimize this risk.
Keywords: Urinary tract infection, urinary catheter, neurosurgery, intensive care, Candida.